2019
DOI: 10.1111/ncmr.12170
|View full text |Cite
|
Sign up to set email alerts
|

There is No Away: Where Do People Go When They Avoid an Interpersonal Conflict?

Abstract: When people avoid conflict, there is no "away." Where do they go physically or mentally? Both engaging and avoiding have a push and a pull. If we knew where avoiders go, we could study the pull of avoidance. This is a descriptive study (N = 446) of interpersonal conflict. We found that physical and mental avoidance appeared with similar frequency, and that they could occur in combination. People often recognized their need for avoidance early, based on the topic being familiar or various signals of trouble. Av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…For instance, participants’ misuse of agreement, detailed in Process Subtheme 1.1 (participant eagerly misjudges agreement with canvasser), may be interpreted as a response to the presence of cognitive dissonance. This interpretation is corroborated by previous findings in conflict management research that indicate that false agreement is a common way to avoid interpersonal conflict (Hample & Hample, 2019; Oetzel et al, 2000; Sillars & Wilmot, 1994). This desire to withdraw from conflict often evidences uncertainty about one’s attitudinal position that may indicate the presence of cognitive dissonance (Roloff & Wright, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…For instance, participants’ misuse of agreement, detailed in Process Subtheme 1.1 (participant eagerly misjudges agreement with canvasser), may be interpreted as a response to the presence of cognitive dissonance. This interpretation is corroborated by previous findings in conflict management research that indicate that false agreement is a common way to avoid interpersonal conflict (Hample & Hample, 2019; Oetzel et al, 2000; Sillars & Wilmot, 1994). This desire to withdraw from conflict often evidences uncertainty about one’s attitudinal position that may indicate the presence of cognitive dissonance (Roloff & Wright, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…Research on conflict interactions has shown that contextual elements are extremely important to the (emotional) course of conflict between people. Examples of such contextual elements are the behavioral strategies to manage the early emergence of disagreements (e.g., attempts to avoid conflict either physically or mentally; Hample & Hample, 2020), the different ways that conflict may start between actors (e.g., jointly or unexpectedly; Hample et al, 2019), or conflict narratives (Lewiński et al, 2018); all of these elements may differ between cultures. Future research should aim to provide a detailed picture of how disagreement may emerge and unfold in different cultures, including a cross-cultural analysis of wider contextual variables that contribute to differential unfolding.…”
Section: Discussionmentioning
confidence: 99%
“…A reluctance to disclose PI could occur if one were embarrassed to disclose they were underpaid or were paid inequitably or if they otherwise wanted privacy (Colella et al, 2007;Exline et al, 2004). Furthermore, individuals avoid having conversations if they feel it will cause interpersonal friction (Hample and Hample, 2020). Thus, while individuals who perceive high pay equity may feel comfortable sharing PI, individuals who perceive low pay equity may be motivated to avoid sharing PI: H2.…”
Section: Introductionmentioning
confidence: 99%